2021
DOI: 10.3390/magnetochemistry7090127
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterisation of Antiferromagnetic Ni2MnAl Heusler Alloy Films

Abstract: Recent rapid advancement in antiferromagnetic spintronics paves a new path for efficient computing with THz operation. To date, major studies have been performed with conventional metallic, e.g., Ir-Mn and Pt-Mn, and semiconducting, e.g., CuMnAs, antiferromagnets, which may suffer from their elemental criticality and high resistivity. In order to resolve these obstacles, new antiferromagnetic films are under intense development for device operation above room temperature. Here, we report the structural and mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The first one is focused on the way how to synthesize these materials. In addition, the conventional techniques including arc and induction melting [10,11] producing the bulk materials, or dc-and rf-sputtering on different types of substrates in a form of thin films [12], there are still efforts for searching Heusler alloys with improved properties leading to involvement of non-traditional preparation technologies. Therefore, in last few years, there is couple of papers showing interesting properties of Heusler alloys prepared either by mechanical alloying (MA) in a form of powders [13,14] or by planar flow casting (PFC) technique having ribbon shapes [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The first one is focused on the way how to synthesize these materials. In addition, the conventional techniques including arc and induction melting [10,11] producing the bulk materials, or dc-and rf-sputtering on different types of substrates in a form of thin films [12], there are still efforts for searching Heusler alloys with improved properties leading to involvement of non-traditional preparation technologies. Therefore, in last few years, there is couple of papers showing interesting properties of Heusler alloys prepared either by mechanical alloying (MA) in a form of powders [13,14] or by planar flow casting (PFC) technique having ribbon shapes [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Even for the full-Heusler alloys, the perfectly-ordered L21 phase can be deformed into the B2 phase by atomically displacing Y-Z elements, the D03 phase by X-Y displacements and the A2 phase by randomly exchanging X-Y-Z elements. We have recently found that Ru2YZ [35], Ni2YZ [36], [37] and Mn2YZ [38], [39] Heusler alloys exhibit AF behavior in their L21, B2 and A2 crystalline ordering phases. By attaching a FM Fe layer to these AF layers, Hex of up to 600 Oe at 100 K, 90 Oe at 100 K and 30 Oe at 100 K for Ru2MnGe, Ni2MnAl and Mn2Val, respectively, have been found.…”
Section: Introductionmentioning
confidence: 99%
“…3 [37]. The Q-factor is defined as the peak intensity measured by X-ray diffraction (XRD) divided by full width at half maximum, which offers a very simple measure to evaluate the crystallinity of Heusler alloys and beyond.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Huminiuc et al grew and characterised polycrystalline Ni 2 MnAl Heusler alloy films [10]. For the demonstration of room-temperature antiferromagnetism, Fe and Co have been used for partial substitution of Ni.…”
mentioning
confidence: 99%